Antisense inhibition of a pectate lyase gene supports a role for pectin depolymerization in strawberry fruit softening - Santiago-Doménech, Nieves (Oxford University Press, 2008)
Cell wall disassembly in softening fruits is a complex process involving the cumulative action of many families of wall-modifying proteins on interconnected polysaccharide matrices. One strategy to elucidate the in vivo substrates of specific enzymes and their relative importance and contribution to wall modification is to suppress their expression in transgenic fruit. It has been reported previously that inhibiting the expression of pectate lyase genes by antisense technology in strawberry (Fragaria×ananassa Duch.) fruit resulted in prolonged fruit firmness. This suggested that pectin depolymerization might make a more important contribution to strawberry fruit softening than is often stated. In this present study, three independent transgenic lines were identified exhibiting a greater than 90% reduction in pectate lyase transcript abundance. Analyses of sequential cell wall extracts from the transgenic and control fruit collectively showed clear quantitative and qualitative differences in the extractability and molecular masses of populations of pectin polymers. Wall extracts from transgenic fruits showed a reduction in pectin solubility and decreased depolymerization of more tightly bound polyuronides. Additional patterns of differential extraction of other wall-associated pectin subclasses were apparent, particularly in the sodium carbonate- and chelator-soluble polymers. In addition, microscopic studies revealed that the typical ripening-associated loss of cell–cell adhesion was substantially reduced in the transgenic fruits. These results indicate that pectate lyase plays an important degradative role in the primary wall and middle lamella in ripening strawberry fruit, and should be included in synergistic models of cell wall disassembly.